PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI MENGGUNAKAN CONTEXTUAL TEACHING LEARNING DI SEKOLAH DASAR - Utami, Nevy Della; Halidjah, Siti; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis study aims to describe how contextual teaching learning can increase writing skill narrative essay of class V students of Primary School Â 03 Pontianak City. This research uses descriptive method with form of action research class (PTK) and is collaborative. This research was conducted for two cycles with each cycle two time meeting. The results of the study design study (RPP) of the cycle I average score 3.06, cycle II average score 3.29. The results of research implementation of the learning cycle I score average of 2.92, cycle II average score 3.32. The result of the research write narrative essay from cycle I mean value 69,44, second cycles II value 80,89. Total mastery reach 90% or 27 people with 23,33% increase from cycle I which only 66,67%. From the data obtained can be concluded that the application of contextual teaching learning can improve the writing skills of student narrative. Thus, research using a contextual teaching learning to learning writing skill narrative essay can increasing writing skill of student narrative.Keywords: Increasing, Contextual Teaching and Learning, Writing Narrative Essay